ATIM-31. PHASE I STUDY OF TUMOR TREATMENT FIELDS AND A PERSONALIZED MUTATION-DERIVED TUMOR VACCINE IN PATIENTS WITH NEWLY DIAGNOSED GLIOBLASTOMA. (5th November 2018) - Hormigo, Adilia; Rubinsteyn, Alex; Kodysh, Julia; Yong, Raymund; Hadjipanayis, Constantinos; Bederson, Joshua; Tsankova, Nadejda; Houldsworth, Jane; Bhardwaj, Nina
Abstract: The tumor microenvironment of a glioblastoma is highly immunosuppressive. Overcoming this immunosuppressive activity seems imperative to a successful treatment. Like other cancers, glioblastoma is capable of generating tumor-specific peptides that can be recognized by the immune system, providing a specific target for antitumor therapy. Glioma vaccines including tumor lysate pulsed dendritic cell-based immunotherapy have proven safe and potentially of clinical value, suggesting that dead cells can confer tumor associated antigens for processing and presentation. Use of TTFields in newly diagnosed glioblastoma increases progression-free survival and overall survival. Among several mechanisms of action, TTFields induces an immunogenic cell death. Therefore, we combined this modality treatment with the standard of care and a personalized vaccine for newly diagnosed glioblastoma with the expectation of improved outcome for the patients. RNA and DNA are extracted from tumor specimens and blood and whole exome sequence and mRNASeq is performed. HLA typing is obtained for each patient. Mutation-derived tumor antigens are identified using computational predictions and ranked according to both predicted HLA binding affinity and expression. A maximum of 10 peptides is selected for each patient vaccine. The vaccine is administered subcutaneously using Poly-ICLC as adjuvant during Temozolomide treatment after radiotherapy with concurrent Temozolomide. We are reporting on the initial safety data for patients who received the mutation-derived tumor antigen vaccine without the use of the TTFields. We have encountered not only novel mutated tumor antigens but also well known driver mutations that are predicted to be immunogenic despite a low mutation load in the GBM patients. The trial is feasible and the vaccine seems well tolerated without unexpected adverse events.